2019
DOI: 10.1111/desc.12825
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying infant vocal imitation: The roles of mouth looking and speaker’s gaze

Abstract: Vocal imitation plays a fundamental role in human language acquisition from infancy.Little is known, however, about how infants imitate other's sounds. We focused on three factors: (a) whether infants receive information from upright faces, (b) the infant's observation of the speaker's mouth and (c) the speaker directing their gaze towards the infant. We recorded the eye movements of 6-month-olds who participated in experiments watching videos of a speaker producing vowel sounds. We found that an infants' tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
(195 reference statements)
3
15
0
Order By: Relevance
“…Furthermore, as the effect of inversion was visible in looking towards the mouth region, it suggests that upright face orientation is especially important for speech perception. In line with previous studies [25,26,27,28,38], our results support the notion that both the specialisation for speech and the specialisation for faces are related in infancy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, as the effect of inversion was visible in looking towards the mouth region, it suggests that upright face orientation is especially important for speech perception. In line with previous studies [25,26,27,28,38], our results support the notion that both the specialisation for speech and the specialisation for faces are related in infancy.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that the effect of inversion was specific to looking towards the mouth region supports the idea that AV speech processing development is related to the emergence of configural face processing. A similar effect was shown by Imafuku and collaborators [38] who found that face inversion makes audiovisual information about vowels more difficult to perceive, which leads to limited imitation. However, their study suggested that inversion affects speech already in 6-month-olds, so earlier than in ours.…”
Section: Discussionsupporting
confidence: 76%
“…Second, developmental changes in laughter production may also reflect social learning processes. Infants as young as six months have been found to mimic sounds produced by their caregivers [32], and infants are highly receptive to caregivers' responses to their pre-linguistic vocalizations [33]. In particular, infants adapt subsequent vocalizations based on social feedback [29] and human adults have a preference for voiced, songlike laughs which are produced during exhalation [24].…”
Section: Discussionmentioning
confidence: 99%
“…We tracked infants' eye movements to assess their EM preference. As an exploratory measure, we also video recorded the infants during the experiment to quantify their babbling and to observe their imitation of the target vowels during the experiment, since a link between attention to the mouth and vowel vocalization has been demonstrated (Imafuku et al, 2019). Spanish and Basque languages provide an ideal test bed for AV vowel processing in bilinguals.…”
Section: Current Studymentioning
confidence: 99%